1991
DOI: 10.1007/bf02549609
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae as a urinary tract pathogen in males and non-pregnant females

Abstract: The role of Streptococcus agalactiae (group B streptococci, GBS) was investigated for a period of one year in different clinical forms of urinary tract infection in males and non-pregnant females over 14 years of age. The pathogen has been isolated in quantities of greater than or equal to 10(5) cfu/ml in midstream voided urine from 32 patients with clinical signs of urinary tract infection and pathologic urinary sediment. In every group of B isolates the antibiotic sensitivity to antimicrobial agents was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…60 Girgitzova et al took culture samples from urine in parallel with feces and ureteral or vaginal swabs. 59 They found that GBS isolates from feces had similar antimicrobial sensitivity profiles to that of the urine and genital isolates, reinforcing that the GI tract is often the reservoir for GBS within the human host. 59 A multicenter study by Vigliarolo et al evaluated incidence of UTIs in adult patients from Argentina.…”
Section: Urinary Tract Infection (Uti) In Non-pregnant and Pregnant Adultsmentioning
confidence: 92%
See 2 more Smart Citations
“…60 Girgitzova et al took culture samples from urine in parallel with feces and ureteral or vaginal swabs. 59 They found that GBS isolates from feces had similar antimicrobial sensitivity profiles to that of the urine and genital isolates, reinforcing that the GI tract is often the reservoir for GBS within the human host. 59 A multicenter study by Vigliarolo et al evaluated incidence of UTIs in adult patients from Argentina.…”
Section: Urinary Tract Infection (Uti) In Non-pregnant and Pregnant Adultsmentioning
confidence: 92%
“…59 They found that GBS isolates from feces had similar antimicrobial sensitivity profiles to that of the urine and genital isolates, reinforcing that the GI tract is often the reservoir for GBS within the human host. 59 A multicenter study by Vigliarolo et al evaluated incidence of UTIs in adult patients from Argentina. 58 They found GBS UTIs in non-pregnant adults were often associated with underlying diseases, of which DM was most common.…”
Section: Urinary Tract Infection (Uti) In Non-pregnant and Pregnant Adultsmentioning
confidence: 92%
See 1 more Smart Citation